Adenosine derived from ecto-nucleotidases in calcific aortic valve disease promotes mineralization through A2a adenosine receptor. (2nd February 2015) - Mahmut, Ablajan; Boulanger, Marie-Chloé; Bouchareb, Rihab; Hadji, Fayez; Mathieu, Patrick
Abstract: Aims: In this study, we sought to determine the role of ecto-nucleotidases and adenosine receptors in calcific aortic valve disease (CAVD). The expression of ecto-nucleotidases, which modify the levels of extracellular nucleotides/nucleosides, may control the mineralization of valve interstitial cells (VICs). We hypothesized that expression of ectonucleotide pyrophosphatase/phosphodiesterase 1 (NPP1), which generates AMP, and 5′-nucleotidase (CD73), an enzyme using AMP as a substrate to produce adenosine, may co-regulate the mineralization of the aortic valve. Methods and results: We have investigated the expression of NPP1 and 5′-nucleotidase in CAVD tissues and determined the role of these ecto-nucleotidases on the mineralization of isolated VICs. In CAVD tissues (stenotic and sclerotic), we documented that NPP1 and 5′-nucleotidase were overexpressed by VICs. In isolated VICs, we found that mineralization induced by adenosine triphosphate was decreased by silencing NPP1 and 5′-nucleotidase, suggesting a role for adenosine. Adenosine and specific A2a adenosine receptor (A2aR) agonist increased the mineralization of VICs. Silencing of A2aR in human VICs and the use of A2aR −/− mouse VICs confirmed that A2aR promotes the mineralization of cells. Also, A2aR-mediated mineralization was negated by the transfection of a mutant dominant-negative Gαs vector. Through several lines of evidence, we next documented that adenosine stimulated the mineralization of VICs through a cAMP/protein kinase A (PKA)/cAMP response element-binding protein (CREB) pathway, and found that CREB positively regulated the expression of NPP1 in a positive feedback loop by physically interacting with the promoter. Conclusion: Expression of NPP1 and 5′-nucleotidase by VICs promotes the mineralization of the aortic valve through A2aR and a cAMP/PKA/CREB pathway.